Cooperative transmission scheme based on GSC for cognitive wireless sensor network - Zhi-chao QIN; Zheng ZHOU; Xiao-chuan ZHAO; Yang ZHANG (Tongxin xuebao)
In response to the features that the sensor nodes are gy-limited and power-constrained in wireless sensor network,a cooperative transmission scheme based on general selection combine(GSC)algorithm was proposed when the channel state information (CSI) was known to the transmitter.The number of cooperative nodes was depended on the GSC algorithm subject to a power constraint at the transmitter,and these selected nodes were scheduled according to the channel sate and individual residual energy.The analys lation results show that the proposed scheme can effectively prolong the network lifetime.